Spontaneous Splenic Artery Rupture as the First Symptom of Systemic Amyloidosis - Bruserud, Øyvind (Case Rep Crit Care, 2021)
Spontaneous splenic rupture is a life-threatening condition leading to a rapidly progressing hypovolemic shock due to intra-abdominal blood loss, with a mortality rate of about 10%. Spontaneous splenic rupture can be caused by widely different disorders including acute and chronic infections, neoplastic disorders, and inflammatory noninfectious disorders. In this case report, we present a 67-year-old male patient with hemorrhagic shock caused by an acute bleeding from the splenic artery. The patient was massively transfused with blood products and fluids and underwent laparotomy for hemostatic control and clinical stabilization. Multiorgan involvement by amyloid light-chain amyloidosis (AL-amyloidosis) caused by plasma cell dyscrasia, specifically with infiltration of the spleen artery, was found to be the underlying cause of his life-threatening bleeding. Based on this case, we discuss the features of serious spleen bleeding, massive transfusion therapy in the intensive care setting, and AL-amyloidosis pathophysiology and treatment.